O budownictwie obronnym województwa łęczyckiego w późnym średniowieczu i czasach nowożytnych – w piętnaście lat później - Kajzer, Leszek (Acta Universitatis Lodziensis. Folia Archaeologica, 1996)
The defensive architecture of the province of Łęczyca (an area located north of Łódź, measuring over 4000 km2 in size) in the Late Middle Ages and in modem times is considered. In 1980 the author published a book on this subject (vol. I in the series „Acta Universitatis Lodziensis”, Folia archaeologica), which contains a catalogue of 77 defensive features (castles, town walls, fortified manor-houses, etc.) and describes their character and principles on which they functioned. Now, after more than 15 years since the appearance of this book, the author reconsideres the problem, scrutinizing the results of recent archaeological field researches. His findings can be summed up as follows: In recent years 31 features have been excavated on the rather small scale. Test excavations for the purpose of conservation, and sondages were dominant. As far as the publication is concerned, the situation is highly unsatisfactory, and in most cases the reports on the researches have not been made public. Though archaeological and archaeological-architectural studies became distincly more intensive, the findings that would invalidate the hypotheses formed in 1980 were limited in number. Major discoveries include a long rectangular brick manor-house at Gaj near Łęczyca, erected on a mound at the close of the 16th or in the early 17th century, and surrounded by a moat, and relics of a hexagonal tower of bricks at Sobota near Łowicz. The tower should probably be dated to the second half of the 14th or to the first half of the 15th century. With regard to the state of knowledge of 1980, the chronology of the features in question had to be slightly altered. Though the title of the book of 1980 refers to the 13th-17th centuries, recent excavations have failed to reveal a feature unquestionably dated to the second half of the 13th century. The earliest fortified residences date from the turn of the 13th/14th centuries, and the latest, from the 18th century. Accordingly, it seems fairly certain that the custom of building manor-houses on mounds originated in the Łęczyca region somewhat later (about 1300) and lasted longer (to about 1800) than has been surmised so far.